Intelligence, creativity, psychological and personal qualities of employees as factors of real achievements - Furman, Anatoliy; Kutsepal, Svitlana; Prykhodko, Tamara; Krylova, Svіtlana; Gliznutsa, Maryna; Vykhovanets, Zorina (IAEME Publication, 2020)
In the work, we analyzed the relationship of indicators of psychometric intelligence and psychometric creativity with intellectual, creative and social achievements. On the other hand, we tried to identify the role of different intellectual abilities and different forms of creativity, taking into account the different measures of their conjugation with real achievements, and also to analyze the role of those personal properties that, related to the peculiarities of organizing different forms of individual mental (conceptual, metacognitive, intentional) experience, act as a condition for real creative achievements of employees. The main approaches to the study of intelligence and creativity in connection with various aspects of individual productivity were examined, the results of studies of the ratio of intellectual and creative abilities were analyzed, and ideas about the role of personal properties as a factor in the employee's real achievements were analyzed.
Keywords: reliability; spiritual intelligence; validity; work performance